The state of world population 2012. By choice, not by chance. Family planning, human rights and development (New York, 2012)
"Family planning is a human right. Yet today some 222 million women in developing countries are unable to exercise that right because they lack access to contraceptives, information and quality services or because social and economic forces prevent them from taking advantage of services even where they are available."